KONTRIBUSI DAYA LEDAK OTOT LENGAN DAN KOORDINASI MATA TANGAN TERHADAP KETEPATAN SERVIS ATAS BOLAVOLI MAHASISWA PENDIDIKAN KEPELATIHAN OLAHRAGA UNIVERSITAS RIAU - Ardiah Juita (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2013)
Problems in the research was started from observation that the researchers encountered in the field,Apparently volleyball players did not exactly serve on the target that was predicted to be influenced byan explosive arm muscles and hand-eye coordination. The purpose of this research is to know theextent of the contribution of an explosive arm muscles and hand-eye coordination with serviceaccuracy of students Sports Coaching Education UR. This type of research is correlational. Thepopulation in this study was 52 Coaching Sports Education Student UR. Using purposive samplingtechnique, the sample on this research was 25 students who could up service. To get the dataresearchers used a medicine ball test, ballwerfen Und-Fangen test and accuracy of up services. TheData obtained were analyzed with simple and double product moment and determinant coefficients todetermine contributions. Based on the analysis of the data it was found that there was a significantrelationship between explosive arm muscles with service accuracy, the results obtained were r.count0,428 > r.table 0,396, with contributions amount 18.28%, and then there was a significantrelationship between hand-eye coordination and service accuracy. The results obtained were rcount0,411 > rtable 0,396, with contributions amount 16,91%, and there was also a significant relationshipbetween explosive arm muscles and hand-eye coordination with service accuracy of student SportsCoaching Education UR, was marked by results obtained R.count 0,533 > R.table 0,396, bycontributions 28,44 %.Key words: explosive arm muscle, hand-eye coordination, volleyball service accuracy.